Monetary policy and exchange rate liberalisation in the Caribbean : preliminary analysis (draft) - Birchwood, Anthony ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 1999)
Examines the importance and timing patterns of various monetary aggregates and prices with respect to their influence on price stability. Focuses on Guyana, Jamaica and Trinidad and Tobago in the aftermath of exchange rate liberalisation.